(untitled) (Journal of the College of Basic Education, 2025)
The conversational implicature in Surah Al-Baqarah due to its extensive use of admonitions and rulings, its discussion of the creation and formation, and its portrayal of the conditions of the People of the Book, polytheists, and hypocrites in a captivating and accessible style that is easy for the audience to understand and contemplate. Therefore, we chose to examine the phenomenon of generalized conversational implicature, which involves non-literal meanings that are common in various contexts, to assess its impact on communication processes.The research, titled "Generalized Conversational Implicature: The Case of Surah Al-Baqarah," is divided into two main chapters. The first chapter explores generalized linguistic terms, while the second chapter investigates generalized quantitative terms. Each chapter contains sections that clarify these concepts with examples, relying on pragmatic analysis methods. The study concludes that generalized conversational implicature is an effective communicative technique that significantly engages the audience, making them receptive and engaged with the text.